Specific versus Nonspecific Solvent Interactions of a Biomolecule in Water - He, Lanhai; Tomaník, Lukáš; Malerz, Sebastian; Trinter, Florian; Trippel, Sebastian; Belina, Michal; Slavíček, Petr; Winter, Bernd; Küpper, Jochen (The journal of physical chemistry letters, 2023)
Solvent interactions, particularly hydration, are vital in chemical and biochemical systems. Model systems reveal microscopic details of such interactions. We uncover a specific hydrogen-bonding motif of the biomolecular building block indole (C8H7N), tryptophan's chromophore, in water: a strong localized N-H···OH2 hydrogen bond, alongside unstructured solvent interactions. This insight is revealed from a combined experimental and theoretical analysis of the electronic structure of indole in aqueous solution. We recorded the complete X-ray photoemission and Auger spectrum of aqueous-phase indole, quantitatively explaining all peaks through ab initio modeling. The efficient and accurate technique for modeling valence and core photoemission spectra involves the maximum-overlap method and the nonequilibrium polarizable-continuum model. A two-hole electron-population analysis quantitatively describes the Auger spectra. Core-electron binding energies for nitrogen and carbon highlight the specific interaction with a hydrogen-bonded water molecule at the N-H group and otherwise nonspecific solvent interactions.